A New Rationale for the Doctrine of Provocation: Applications to Cases of Killing an Unfaithful Spouse - Rosenberg, Roni (Columbia Journal of Gender and Law, 2019)
In many states in the United States, a man who killed his wife upon discovering that she had been unfaithful to him can rely upon the provocation defense so long as he can demonstrate that sudden discovery of the infidelity affected his subjective judgement. This essay proposes a different rationale for the doctrine of provocation, which negates the reliance on the provocation defense in the case of an unfaithful spouse. The proposed rationale is neither excuse, which focuses on reduced guilt due to the defendant’s loss of self-control, nor justification, in that the victim was partly responsible for his or her own death. Rather, the rationale rests upon an understanding of why murder is prohibited and an examination of the protected values at the core of the offense of murder.